Justification of Violence Beliefs and Social Problem-Solving as Mediators between Maltreatment and Behavior Problems in Adolescents - Calvete, Esther (The Spanish Journal of Psychology, 2007)
This study examined whether justification of violence beliefs and social problem solving mediated between maltreatment experiences and aggressive and delinquent behavior in adolescents. Data were collected on 191 maltreated and 546 nonmaltreated adolescents (ages 14 to 17 years), who completed measures of justification of violence beliefs, social problem-solving dimensions (problem orientation, and impulsivity/carelessness style), and psychological problems. Findings indicated that maltreated adolescents’ higher levels of delinquent and aggressive behavior were partially accounted for by justification ofviolence beliefs, and that their higher levels of depressive symptoms were partially mediated by a more negative orientation to social problem-solving. Comparisons between boys and girls indicated that the model linking maltreatment, cognitive variables, and psychological problems was invariant.
Keywords: Maltreatment; Problem-solving; Beliefs; Aggressive and delinquent behaviours; Depression